In situ operando investigations of the thermal instability mechanisms of a deformed Ti-48Al alloy - Krishnan, P.S. Sankara Rama (2025)
TiAl based alloys are currently deployed in extreme service environments, such as jet engine turbine blades. The microstructure of these alloys is a two-phase lamellar structure, comprising of the majority γ-TiAl and the minority α2-Ti3Al phases. Understanding the microstructural evolution at high stresses and elevated temperatures is a key requirement to develop the next generation of these alloys. In situ hot stage TEM studies are reported of the mechanisms of lamellar instability and changes in phase fraction of both cold worked and undeformed Ti-48Al alloys. The effect of cold working on the kinetics of this instability has also been determined. Cross-sectional TEM samples are prepared on custom designed MEMS chips and in situ heating studies carried out. These results show that neck formation, break-up of lamellae, and spheroidization are the dominant mechanisms of microstructural instability. An increase in γ-TiAl phase content is also observed. The strain energy present in the α2 and γ lamellae in cold worked samples results in microstructural instabilities occurring at lower temperatures in cold worked samples. These findings can be used to design new alloys with improved high temperature stability.